Assessment of heavy metal concentrations in imported marine fish species consumed in Ogun state, Nigeria - Adebowale, Adetola Quddus; Odubote, Mary Opeyemi; Adefabi, Adedapo Samson (Syiah Kuala University, 2024)
Fish is an affordable protein source in developing countries such as Nigeria, however, human activities like mining, agriculture, and industrial discharges negatively impact these aquatic resources and their environment. Heavy metals leach into the ocean and accumulate in fish, potentially causing health issues for those who consume them. The present study evaluated the heavy metal concentrations in five commercially important and highly consumed fish species (Clupea pallasii,Merluccius productus,Gadus chalcogrammus, Scomber scombrus,Trachurus murphyi) in Nigeria. The study was conducted between August 2021 to January 2022, and Mn, Fe, Zn, Pb, Cd levels were sampled in a total of 50 fish using the AA 240 Fanst Sequential Atomic Absorption Spectrophotometer and expressed as mg/kg wet weight. Among the heavy metals estimated in all fish samples, Mn was the most prevalent, while Zn was relatively the lowest. Pb (6.39 mg/kg), Cd (1.39 mg/kg), and Fe (5.59 mg/kg) concentrations exceeded the FAO and WHO regulatory limits and may be deleterious to human health. Therefore, while essential as a protein source, the presence of heavy metals exceeding recommended limits in these commonly consumed imported fish species raises public health concerns. This study emphasizes the crucial need for stricter regulations and consistent monitoring of imported fish to guarantee their safety and consumer well-being in Nigeria.